2021
DOI: 10.1097/pcc.0000000000002793
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Children With Necrotizing Pneumonia

Abstract: In this study, we describe the characteristics and outcomes of pediatric necrotizing pneumonia in the United States. DESIGN AND SETTING:A retrospective analysis of the Healthcare Cost and Utilization Project 2016 Kids Inpatient Database was performed. The Kids Inpatient Database is a large deidentified hospital discharge database of pediatric patients in the United States. PATIENTS:The database was filtered using International Classification of Diseases, 10th Edition code J85.0 to identify necrotizing pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…Etiological analysis suggested that the four most commonly isolated organisms were M. pneumoniae, S. pneumoniae, S. aureus, and P. aeruginosa in all patients, which are similar to those of a recent study 21 ; therefore, it is important to provide empiric antibiotic coverage for these organisms. The composition of the pathogens among the three groups varied widely.…”
Section: Discussionsupporting
confidence: 83%
“…Etiological analysis suggested that the four most commonly isolated organisms were M. pneumoniae, S. pneumoniae, S. aureus, and P. aeruginosa in all patients, which are similar to those of a recent study 21 ; therefore, it is important to provide empiric antibiotic coverage for these organisms. The composition of the pathogens among the three groups varied widely.…”
Section: Discussionsupporting
confidence: 83%
“…5 The retrospective analysis by Manette et al in 2016 showed half of the patients with necrotizing pneumonia required chest tube drainage, while 6% required video-assisted thoracoscopic surgery. 6 The most common organism identified in this study was streptococcus pneumonia (12.6%) followed by staphylococcus aureus (9.2%) which couldn't be isolated in our case which can be explained by upfront administration of antibiotics before admission. The median age of children with necrotizing pneumonia was 3.2 years in an observational study conducted by Blanco-Iglesias et al where 49 of 51 patients presented with pleural effusion, the causative agent was isolated in two-thirds of cases and pneumococcus was the commonest.…”
Section: Discussioncontrasting
confidence: 52%
“…Some viruses and fungi like influenza, parainfluenza, adenovirus, respiratory syncytial virus, Herpes group (including Cytomegalovirus, Varicella-Zoster and the Epstein–Barr Virus), Aspergillus spp., Candida spp., Histoplasma capsulatum , Coccidioides spp., Blastomyces spp. and Cryptococcus neoformans can also cause NP [ 6 , 10 ]. And a synergy between viruses and bacteria is common and sometimes lethal.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…A study in Taiwan found that no underlying diseases may predict the occurrence of necrosis and/or abscess independently [ 5 ]. However, a recent study has shown that NP tended to occur in children with a complex chronic condition, and the mortality rate was higher than that of NP in previously healthy children [ 6 ]. NP is characterized by necrosis and liquification of lung parenchyma and loss of the normal pulmonary parenchymal architecture [ 7 ].…”
Section: Introductionmentioning
confidence: 99%